Padrões relacionais, maus tratos na infância e regulação emocional em mulheres vítimas de violência conjugal - Poletto, Mariana Pasquali (2016)
This study proposes a comprehensive model of transgenerationality of family violence that considers not only the experience of abuse, but also the linking forms in childhood that originate from the parenting styles deficit. Still, this study demonstrates the deleterious consequences of these relational patterns in adult attachment and experience of intimate partner violence (IPV). This master thesis search from two empirical studies: 1) analyze the contribution of mistreatment in childhood, type of attachment in childhood and parenting styles for emotional dysregulation in adulthood and 2) to evaluate the effect of the difficulties of regulation emotional post-traumatic symptoms in women victims of conjugal violence. To do this, correlation analyzes were performed, and multiple logistic regression analyzes. The results point to significant contributions of deficit parenting styles and ill-treatment in childhood for emotional dysregulation in adulthood and insecure adult attachment patterns. Still, relationships were found between emotional dysregulation and post-traumatic symptoms in women victims of conjugal violence. Some limitations should be considered for the sample size and the absence of a control group. In future research, aims at increasing the sample, inclusion of a control group matched for age and education, so that you can identify mediating variables in the development of a secure attachment and adaptive emotion regulation strategies.